Small subunit isoform diversity underlies structural heterogeneity in native plant Rubisco - Thomas Reynolds; Zhemin Zhang; Dušan Živković; Steven Kelly; Jani R. Bolla (Proceedings of the National Academy of Sciences, 2026)
Ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco), the most abundant protein on Earth, catalyzes the fixation of CO 2 in photosynthesis. In terrestrial plants, Rubisco assembles as a hexadecameric complex (L 8 S 8 ), comprising eight large subunits (LSu) and eight small subunits (SSu). While LSu is encoded by a single chloroplastic gene, a nuclear multigene family results in diverse SSu protein isoforms, but structural evidence is currently lacking for Rubisco holoenzyme SSu heterogeneity. In this study, utilizing native Rubisco purified from Arabidopsis thaliana , we employed high-resolution mass spectrometry and cryo–electron microscopy to demonstrate that multiple SSu isoforms can co-assemble within individual Rubisco complexes. We unambiguously identify the composition of these mixed-isoform complexes and elucidate isoform-specific structural interactions at near-atomic resolution. The structural heterogeneity in plant Rubisco established here will underpin future research to establish the impact of SSu diversity on kinetic and functional plasticity of Rubisco activity under diverse environmental conditions.